The vasculature of neurogenic niches: properties and function - Karakatsani, Andromachi; Álvarez-Vergara, María I.; Ruiz de Almodóvar, Carmen (Cells & development, 2023)
In the adult rodent brain, neural stem cells (NSCs) reside in the subventricular zone (SVZ) of the lateral ventricles and the subgranular zone (SGZ) of the hippocampus. In these areas, NSCs and their progeny integrate intrinsic signals and extrinsic cues provided by their microenvironment that control their behavior. The vasculature in the SVZ and SGZ, and the choroid plexus (ChP) in the SVZ, have emerged as critical compartments of the neurogenic niches as they provide a rich repertoire of cues to regulate NSC quiescence, proliferation, self-renewal and differentiation. Physical contact between NSCs and blood vessels is also a feature within the niches and supports different processes such as quiescence, migration and vesicle transport. In this review, we provide a description of the brain and choroid plexus vasculature in both stem cell niches, highlighting the main properties and role of the vasculature in each niche. We also summarize the current understanding of how blood vessel- and ChP-derived signals influence the behavior of NSCs in physiological adulthood, as well as upon aging.